Dentistry Amidst the COVID-19 Pandemic: Knowledge, Attitude, and Practices Among the Saudi Arabian Dental Students - Almulhim, Basim; Alassaf, Abdullah; Alghamdi, Sara; Alroomy, Riyadh; Aldhuwayhi, Sami; Aljabr, Abdullah; Mallineni, Sreekanth Kumar (Frontiers in Medicine, 2021)
Background: The recent pandemic outbreak has created a huge impact on dentistry. Dental students and dental professionals are at a higher risk because dental practice comprises close communication and widespread exposure to blood, saliva, and other body fluids. It is imperative to evaluate the knowledge and perceptions regarding Coronavirus (COVID-19) among budding dentists. Aim: To assess the knowledge, attitude, and practices of dental students regarding dental practices during COVID-19. Materials and methods: A cross-sectional questionnaire-based study was conducted among undergraduate students in Riyadh, Saudi Arabia. An online questionnaire consisting of demographic, knowledge, and attitude-based questions were circulated among the study population, and the responses for the knowledge and attitude were scored. Their mean scores were then calculated. Chi-square test and nonparametric tests were computed using SPSS version 21 software, and p-values<0.05 were considered statistically significant. Results: 388 undergraduate dental students have participated in the study from Saudi Arabia. 68% of the respondents believed that they had sufficient knowledge regarding COVID-19. The mean score for knowledge was 5.84 out of 7. Females (6.24) scored statistically significantly higher than males (5.55, p<=0.001). The mean attitude score was 6.34 out of 9. 93% were using PPE models, while 95% maintained social distancing. Out of all the participating dental students, only 16% were willing to treat patients during the pandemic, and 28% did not want to treat patients, 28% preferred teledentistry. The majority (44%) of dental undergraduates were willing to handle only emergency cases. Conclusion: Accurate knowledge and attitude regarding COVID-19 and diversified opinion on preventive practices during the pandemic period among budding dental professionals evident from Saudi Arabia. Mixed opinions were witnessed among them in seeking help from professional societies. The majority of dental undergraduates were willing to handle only emergency cases.